SOIL SPATIAL VARIABILITY OF SOME SOIL PROPERTIES USING FACTOR ANALYSIS IN FEDERAL COLLEGE OF FORESTRY MECHANIZATION, KADUNA RESEARCH FARM - Dare, Akinrinshola; Okechalu, Samson O.; Amos, Bako; Ademola, Thompson Oluwole; Luka, G. Lapkat (FUDMA Journal of Sciences, 2020)
This paper shows the spatial variability of soil properties and factors that contribute to the pattern of variability in Federal College of Forestry Mechanization Research farm. Nine (9) Soil samples were obtained from various points on the farm using random sampling procedure and these samples were subjected to further for laboratory analysis to determine the particle size fraction, soil pH, organic matter content, and from the data obtained was used to determine the Wilting Point (WP), Saturation Capacity (SC), Field Capacity (FC), Available Water Content (AW), Soil Hydraulic Conductivity (SHC), and Bulk density (BD) using SOILWAT software. Descriptive statistics and factor analysis techniques was used to analyze the data obtained, the coefficient of variation ranged from 3.045 to 61.825% and factor analysis showed that the variability of the soil properties is as a result of the textural characteristics, and organic matter.